COLLETOTRICHUM DISEASE OF ELEPHANTOPUS SCABER AND ITS EFFECT ON SECONDARY METABOLITES - T.R. PARASHURAMA; M. M. VASANTHAKUMARI; M.B. SHIVANNA (International Journal of Pharma and Bio Sciences, 2013)
Elephantopus scaber is an important medicinal herb in India which is extensively used in the traditional system of medicine, for the treatment of various diseases and disorders in humans. A systematic study was carried out to determine the causal organism that caused foliar disease in Bhadra Wildlife sanctuary, the incidence and severity of foliar disease in E. scaber growing extensively in its natural habitat during 2006-09. The spatial distribution of foliar fungal disease in E. scaber was determined by modified Taylor’s power law. The seedborne nature and transmission of the causal organism and its management by seed dressing with fungicides was also determined. The secondary metabolite content in infected foliages was determined. The present study indicated that Colletotrichum dematium is a major foliar disease causing pathogen in E. scaber. The foliar disease severity is high in Kagemanegiri forest region during November-December. The disease incidence is homogeneously distributed in all the nine forest regions of the study area. The causal pathogen is seedborne and seed transmitted and could be managed with Bavistin or Captra. The analysis of secondary metabolites in diseased foliages indicated that steroids decreased with increase in infection due to C. dematium, while alkaloids, phenols and flavonoids increased upon infection. The study also suggested that foliar infection by C. dematium might cause considerable damage to E. scaber plants and could alter the quality of secondary metabolites.